Factors Affecting Respondents’ Participation in Farmers Field Schools in Khartoum State, Sudan - Bello, Abdel Raouf Suleiman (Advances in Social Sciences Research Journal, 2020)
This study was conducted to determine the socioeconomic factors influencing farmer participation in the Farmer Field Schools (FFS) program in Bahari Locality of Kharoum State, Sudan. Eighty farmers were selected randomly and interviewed for this study where Frequency distribution and multiple regressions were used to analyze the data. The study findings indicate that more than 95.0% of respondents were economically active, 88.7% had formal education, 83.0% managed their own farm and 86.3% were currently married. Multiple regressions revealed that the level of participation in FFS was significantly associated with education, farm ownership, farm size, and the period of residency. In addition, the data showed that the level of application of received agricultural innovations was significantly associated with education level, farm ownership, farm size, and total income. The study recommended some interventions to improve and develop the practices and approach of the FFS approach.